Hospital Readiness in Several Countries in Dealing with COVID-19 Pandemic: A Systematic Review - Siti Riri Shafira; Anhari Achadi (Humanistic Network for Science and Technology (HNST), 2022)
The current COVID-19 pandemic has made the world face the most difficult situation in this decade. Millions of people infected with COVID-19 are of concern to the medical world. The role of the hospital is not spared from this, a place for treatment and infection control. Hospital readiness is very important to respond effectively to this pandemic. The purpose of this systematic review is to find out how far the current hospital readiness in dealing with the COVID-19 pandemic. The analysis was guided by the Rapid Hospital Readiness Checklist developed by WHO to identify preparation and preparedness response to the pandemic that consisted of 12 components i.e leadership, coordination, surveillance, risk communication, patient surge, administration, human resources, primary care, patient management, occupational safety, diagnosis, and infection prevention. The method used was systematic review using PRISMA and search articles through ScienceDirect, Scopus, and Proquest using the keywords